Shielding Parenteral Nutrition Solutions From Light: A Randomized Controlled Trial. (August 2015) - Laborie, Sophie; Denis, Angélique; Dassieu, Gilles; Bedu, Antoine; Tourneux, Pierre; Pinquier, Didier; Kermorvant, Elsa; Millet, Véronique; Klosowski, Serge; Patural, Hugues; Clamadieu, Catherine; Brunhes, Anne; et al.
Introduction: Oxidant stress is implicated in the pathogenesis of bronchopulmonary dysplasia (BPD). Light induces peroxide generation in parenteral nutrition (PN) solutions, creating an oxidant stress. Shielding PN from light decreases its peroxide content, which has nutrition and biochemical benefits in animals and humans. This study aims at determining whether full light protection of PN decreases the rate of bronchopulmonary dysplasia and/or death in very low-birth-weight infants. Methods : Multicenter randomized controlled trial of photoprotection, using amber bags and tubing initiated during compounding of PN and maintained throughout infusion in the light-protected (LP) group. The control group (light exposed [LE]) received PN exposed to ambient light. Depending on centers, lipids were infused either separately or as all-in-one PN. Results : In total, 590 infants born <30 weeks gestational age were included. At randomization, LE and LP groups did not differ clinically except for maximal FiO2 before 12 hours. The rate of BPD/death was not different between groups at 28 days (77% LP vs 72% LE, P = .16) or at 36 weeks corrected age (30% LP vs 27% LE, P = .55). Multivariate analysis showed no significant effect of photoprotection on BPD and/or death. The rate of BPD/death was significantly lower (odds ratio, 0.54; 95% confidence interval, 0.32–0.93; P = .02) in infants receiving all-in-one PN vs those who received lipids separately. Conclusion : This study did not show significant beneficial effects of photoprotection. Since the decreased rate of BPD/death found with all-in-one PN relates to a center-dependent variable, this warrants further investigation.